Options for modeling the respiratory system: inserts, scaffolds and microfluidic chips - Sedláková, Veronika; Kloučková, Michaela; Garlíková, Zuzana; Vašíčková, Kateřina; Jaroš, Josef; Kandra, Mário; Kotasová, Hana; Hampl, Aleš (Drug discovery today, 2019)
The human respiratory system is continuously exposed to varying levels of hazardous substances ranging from environmental toxins to purposely administered drugs. If the noxious effects exceed the inherent regenerative capacity of the respiratory system, injured tissue undergoes complex remodeling that can significantly affect lung function and lead to various diseases. Advanced near-to-native in vitro lung models are required to understand the mechanisms involved in pulmonary damage and repair and to reliably test the toxicity of compounds to lung tissue. This review is an overview of the development of in vitro respiratory system models used for study of lung diseases. It includes discussion of using these models for environmental toxin assessment and pulmonary toxicity screening.
Keywords: laboratoř na čipu; Respiratory System; Microfluidics; Models, Biological; dýchací soustava; Lab-On-A-Chip Devices; Animals; biologické modely; Cell Culture Techniques; Humans; tkáňové podpůrné struktury; Tissue Scaffolds; lidé; zvířata; buněčné kultury; mikrofluidika